Fifteen-Year Journey to High Reliability in Pathology and Laboratory Medicine. (September 2018) - Middleton, Lavinia P.; Phipps, Ron; Routbort, Mark; Prieto, Victor; Medeiros, L. Jeffrey; Riben, Michael; Contreras, Alejandro; Kelley, James; Patel, Keyur; Bingham, John; Wagar, Elizabeth A.
Many high-reliability organizations in industries outside of health care have sustained high levels of excellence and prevention of harm while managing complex systems and risk. To date, no health care organizations has organized its efforts to achieve highly reliable results despite several decades of improvement science. Laboratorians were early adopters of quality initiatives and process improvements. In the late 1990s, the Division of Pathology and Laboratory Medicine at The University of Texas MD Anderson Cancer Center embarked on a major effort to improve quality and patient safety and to reduce waste. This article describes the institution's journey toward approaching high reliability with the intent to share not only the tools and best practices, but also the ongoing reassessment of the problems detected on the journey. The authors hope that their experience will help the reader develop interventions to adapt in their own environment to facilitate more optimal patient care.